Hacia la convergencia mundial del marco conceptual para la preparación de los estados financieros - Díaz Durand, Mario; Gil, Jorge José; Vílchez Olivares, Percy (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
Due to the current globalization in business and investments that generate a highly interrelated business world, it is a must to have a common standard in accounting that brings transparency and the real use of information. According to that, this article presents a comparative analysis of the conceptual framework for the preparation and presentation of financial statements of the two important international accounting models of normative use: the accounting standards established by the FASB and the IASB. The conceptual framework provides a guideline to prepare and present financial statements and at the same time it is a basis for the enactment of international financial reporting standards. To this day, there are some convergence agreements on conceptual frameworks between FASB and IASB, in charge of producing standards, which implies joint work in relation to their respective frameworks, with the purpose of developing a better conceptual framework, common for both institutions. With respect to this, in the article we can find proposals and reflections related to the convergence of conceptual frameworks, in order to enable the feasibility of a convergent framework as an important document in the revision and the issuance process of future international financial reporting standards.

Debido a la continua globalización de los negocios y la globalización de las inversiones, que genera un mundo de los negocios altamente interrelacionado, es imprescindible contar con estándares comunes en contabilidad que mejoren la transparencia y la utilidad de la información. En ese sentido, el presente artículo presenta un análisis comparativo del marco conceptual para la preparación y presentación de los estados financieros de los dos modelos contables internacionales importantes de uso normativo: las normas contables emitidas por el FASB y el IASB. El marco conceptual proporciona una guía para preparar y presentar estados financieros y sirve de base para emitir normas internacionales de información financiera. A la fecha existen acuerdos de convergencia de marcos conceptuales, entre los organismos emisores de normas FASB y el IASB, lo cual implica un trabajo conjunto sobre sus respectivos marcos conceptuales, con la finalidad de desarrollar un mejor marco conceptual que sea común para ambas entidades. Al respecto, en el artículo se plantean propuestas y reflexiones vinculadas al proceso de convergencia de marcos conceptuales, para aproximar la viabilidad de un marco conceptual convergente como documento base en el proceso de revisión y emisión de futuras normas internacionales de información financiera.
Towards a global convergence of the conceptual framework for preparing financial statements
Keywords: Marco conceptual; Convergencia; Sistemas normativos; Armonización; Normas contables; Organismos emisores de normas; https://purl.org/pe-repo/ocde/ford#5.02.04